THE POSITION OF THE WORLD HEALTH ORGANIZATION ON THE DEVELOPMENT OF NURSING AND MIDWIFERY - T.V. Kaigorodova; E.V. Kirsanova (Педиатрическая фармакология, 2011)
The article analyzes the current role of nurses in the world and presents the position of the World Health Organization concerning nursing on the basis of the basic documents on this issue over the last 10 years. Key words: nursing, nurses, public health organization, World Health Organization, policy documents.